Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/v11070616
|View full text |Cite
|
Sign up to set email alerts
|

Human Adenovirus Serotype 5 Is Sensitive to IgM-Independent Neutralization In Vitro and In Vivo

Abstract: Human adenovirus 5 (HAdV-5) is used as a vector in gene therapy clinical trials, hence its interactions with the host immune system have been widely studied. Previous studies have demonstrated that HAdV-5 binds specifically to murine coagulation factor X (mFX), inhibiting IgM and complement-mediated neutralization. Here, we examined the physical binding of immune components to HAdV-5 by nanoparticle tracking analysis, neutralization assays, mass spectrometry analysis and in vivo experiments. We observed that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Recently, Tian et al demonstrated that the most abundant Gla domain-containing plasma protein, prothrombin (FII), is able to bind to species C HAdv-C1, HAdv-C2, HAdv-C6, and HAdv-C57 with higher affinity than FX [19], thus potentially pointing to a high significance of HAdv interactions with blood coagulation factors for certain step(s) in the virus life cycle. Because natural IgM are one of the most abundant plasma proteins, the binding of IgM and coagulation FX to HAdv-C5 appears to be a competing process, since low amounts of IgM were still found to associate with HAdv-C5 virions (as demonstrated by mass spectrometry of HAdv-C5 virions incubated with mouse serum) even in the presence of coagulation FX [21]. Because natural IgM are one of the most abundant plasma proteins, the binding of IgM and coagulation FX to HAdv-C5 appears to be a competing process, since low amounts of IgM were still found to associate with HAdv-C5 virions (as demonstrated by mass spectrometry of HAdv-C5 virions incubated with mouse serum) even in the presence of coagulation FX [21].…”
Section: Humoral Factors Affecting Hadv Bio-distribution After Intravmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Tian et al demonstrated that the most abundant Gla domain-containing plasma protein, prothrombin (FII), is able to bind to species C HAdv-C1, HAdv-C2, HAdv-C6, and HAdv-C57 with higher affinity than FX [19], thus potentially pointing to a high significance of HAdv interactions with blood coagulation factors for certain step(s) in the virus life cycle. Because natural IgM are one of the most abundant plasma proteins, the binding of IgM and coagulation FX to HAdv-C5 appears to be a competing process, since low amounts of IgM were still found to associate with HAdv-C5 virions (as demonstrated by mass spectrometry of HAdv-C5 virions incubated with mouse serum) even in the presence of coagulation FX [21]. Because natural IgM are one of the most abundant plasma proteins, the binding of IgM and coagulation FX to HAdv-C5 appears to be a competing process, since low amounts of IgM were still found to associate with HAdv-C5 virions (as demonstrated by mass spectrometry of HAdv-C5 virions incubated with mouse serum) even in the presence of coagulation FX [21].…”
Section: Humoral Factors Affecting Hadv Bio-distribution After Intravmentioning
confidence: 99%
“…Indeed, HAdv-C5 mutants unable to bind coagulation FX were shown to be inactivated in fresh mouse and human serum via a natural IgM-and complement-dependent mechanism (reviewed in detail in this issue by Allen & Byrnes [20]). Because natural IgM are one of the most abundant plasma proteins, the binding of IgM and coagulation FX to HAdv-C5 appears to be a competing process, since low amounts of IgM were still found to associate with HAdv-C5 virions (as demonstrated by mass spectrometry of HAdv-C5 virions incubated with mouse serum) even in the presence of coagulation FX [21]. Although coagulation FX and natural IgM are the principal blood factors that bind to HAdv in the blood after intravenous virus administration to nonimmune hosts, these factors do not protect the virus from neutralization by HAdv-specific neutralizing antibodies in HAdv-C5 immune hosts.…”
Section: Humoral Factors Affecting Hadv Bio-distribution After Intravmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above viruses, the sensitivity of human adenovirus 5 to AP-mediated neutralization was also examined recently. The results showed that the pathway is indeed important for the neutralization of the virus [45]. It is known that AP synergizes with CP and LP in targeting pathogens.…”
Section: Alternative Pathway-mediated Neutralization Of Virusesmentioning
confidence: 86%
“…AdV‐5 is normally stable when incubated in mouse serum but, when FX is blocked, AdV‐5 strongly activates complement and becomes neutralized via a mechanism that requires both natural IgM and the classical complement pathway . In some circumstances, AdV‐5 may also activate complement independently of antibodies, via the alternative pathway . Following complement activation, C3b and C4b become covalently attached to AdV‐5, and this opsonization by complement can both interfere with virus binding to cells and induce intracellular neutralization .…”
Section: Vitamin K‐dependent Coagulation Factorsmentioning
confidence: 99%